Pengaruh Kualitas Pelayanan PT. Angkasa Pura I terhadap Kepuasan Penumpang di Bandar Udara Internasional Lombok, Praya - Sandriana Marina; Dika Risit Maulana; Imam Ozali (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
The purpose of this study is to identify the effect of service quality topassengers’ satisfaction at Lombok Internasional Airport, Praya. The study applied quantitative method by distributing questionaires to 154 passengers of Citilink and Batik airlines from Lombok to Halim. The result of the study shows that there is a strong correlation betwen service quality and passengers’ satisfaction. The contribution value of service quality is 52,1% towards passengers’ satisfaction at Lombok International Airport, Praya.